Studi Komparasi Strategi Snowball Throwing DanStrategi The Power Of Two Terhadap Hasil BelajarIpa Siswa Kelas Iv Sdn 4 JambanganGrobogan Tahun 2015/2016 - Yudiantari, Feri Indri, Drs. H. Mulyadi Sri Kamulyan, M.Pd (2016)
This study aims to describe: (1) the effect difference between strategy Snowball Throwing and strategies The Power of Two on learning outcomes sains class IV students of SDN 4 Jambangan Grobogan year 2015/2016. (2) a better strategy between strategy Snowball Throwing and strategies The Power of Two on learning outcomes sains class IV students of SDN 4 Jambangan Grobogan know 2015/2016. This study included a quantitative study with an experiment model.The research subject graders VA and VB SD Muhammadiyah 1 Surakarta Ketelan.Data collection techniques using the technique of test, documentation. Test instrument is used to test the validity and reliability testing. Data analysis technique using the t-test technique which preced analysis test prerequisite, that is the balance test and normality test. From the results of data analysis with a significance level of 5% there iseffect difference between strategy Snowball Throwing and strategies the power of two the learning outcomes sains class IV students of SDN 4 Jambangan Grobogan with t_tabel>t_hitung, ie2,024 >2,181. The mean scores between grade class are taught using the strategy snowball throwing and classes are taught using the strategy of the power of two ie80<87. The conclusion of this study were (1) there iseffect difference between strategy snowball throwing and strategies the power of two on learning outcomes sains class IV students of SDN 4 Jambangan Grobogan year 2015/2016.(2) strategiesThe Power Of Two better than Snowball Throwing strategy against the results of students' sains learning class IV SDN 4 Jambangan Grobogan year 2015/2016. Keywords: Learning Outcomes Sains, Strategies Snowball Throwing, Strategy The Power of Two.